A new record of Cyrtodactylus soni Le, Nguyen, Le & Ziegler, 2016 (Reptilia: Squamata: Gekkonidae) from Hoa Binh province and threat assessment - Vinh, Luu Quang (Academia Journal of Biology, 2018)
A new population of the Son’s Bent–toed Gecko (Cyrtodactylus soni), an endemic species of Vietnam, is reported for the first time from Hoa Binh province based on three adult male specimens collected in June 2018 in a karst cave of Dong Tam commune, Lac Thuy district. The population of this species in Hoa Binh province is threatened by habitat loss through converting forest to agriculture and quarrying of limestone. Assessment of population status in the study area is urgently needed to provide baseline data for conservation measures.